Exploring the demographic and risk profile of ocular diseases in a tertiary healthcare setting in Pakistan: a gender and age-based analysis - Zahir, Salman (International Journal of Pathology, 2023)
Background: Early diagnosis is necessary for most eye diseases to prevent blindness. Healthcare services should be tailored based on the prevalence and incidence of ophthalmic disease in that region. To investigate the prevalence of ophthalmic diseases among patients seeking treatment at a tertiary care hospital and to identify the risk factors associated with their development, with a focus on age and gender stratification. Materials and Methods: This hospital-based cross-sectional study examined all patients who visited the outpatient department of ophthalmology at a tertiary care hospital between August and November 2022 (i.e., over a period of four months). Each participant provided voluntary verbal informed consent before being examined by an ophthalmologist and optometrist. Information about the patients was gathered using a Performa, and the data was later analyzed using MS Excel Spreadsheet and SPSS (Version 26). Results: Two thousand ophthalmic patients (n=2000) (100%), whose ages ranged from 5 to >65 years, with a mean age of 50.44 + 17.08 years, were studied; 940(47%) males and 1060(53%) females. The distribution of ocular diseases identified via ophthalmological examinations showed that most prevalent ocular morbidity was cataract 450 (22.5%), followed by refractive errors 430 (21.5%). Other prevalent ocular diseases included pterygium 240 (12%), bacterial conjunctivitis 220 (11%), vernal kerato-conjunctivitis 180 (9%), glaucoma 120 (6%), and eyelid diseases 110 (5.5%). Reported significant risk factors for diagnosed eye disorders among study participants included aging, vitamin A deficient diet, excessive screen time, pollution, infections, past ocular disease, family history of eye diseases, poor hygiene, seasonal allergies, trauma, diabetes, and hypertension. Conclusion: Prevalence of ocular diseases was higher in women than in men. The most prevalent ocular morbidity was cataract.